Self-Reported Voluntary Blame-Taking: Kinship Before Friendship and No Effect of Incentives - Schneider, Teresa; Sauerland, Melanie; Merckelbach, Harald; Puschke, Jens; Cohrs, J. Christopher (Frontiers in Psychology, 2021)
Inspired by theories of prosocial behavior, we tested the effect of relationship status and incentives on intended voluntary blame-taking in two experiments (Experiment 2 was pre-registered). Participants (NE1 = 211, NE2 = 232) imagined a close family member, a close friend, or an acquaintance and read a scenario that described this person committing a minor traffic offence. The person offered either a monetary, social or no incentive for taking the blame. Participants indicated their willingness to take the blame and reasons for and against blame-taking. Overall, a sizable proportion of participants indicated to be willing to take the blame (E1: 57.8%; E2: 34.9%). Blame-taking rates were higher for family members than close friends or acquaintances in both experiments, as expected. Unexpectedly, there was no difference between a close friend and an acquaintance in Experiment 2. Social incentives did not have an effect on voluntary blame-taking in either experiment. Neither did we find an interaction between relationship status and incentives. The results highlight the importance of kin relationships in the context of voluntary blame-taking.